Low-carbon steel salt bath vanadinizing method and application
After the low -carbon steel is processed, the high -hardness seepage layer is formed on its surface, which solves the problem of insufficient surface hardness and abrasion resistance of low -carbon steel. Effect.
Patent Information
- Application Number
- CN202411475526.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-22
AI Technical Summary
The existing nitriding and carburizing technologies are difficult to form a surface layer with high hardness and wear resistance on low carbon steel, and the traditional vanadium filtration process has a great limitation on the application of low carbon steel.
After the low -carbon steel is processed, NACL, CACL2, NAF, V2O5, and AL powder are used to prepare melting salt, and the replacement reaction is replaced with AL and V2O5 Perform osmotic treatment to form a high -hardness seepage layer.
The hardness and abrasion resistance of low-carbon steel is significantly improved. The hardness of the osmotic layer is between 2700 and 3360HV, and the wear rate is 0.1 ~ 1.5 × 10-15m3/nm, which is much higher than the performance of the traditional osmotic process.
Smart Images

Figure CN119351938A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coatings, and in particular relates to a method and application of salt bath vanadiumizing of low carbon steel. Background Art
[0002] Low carbon steel has been widely used in various shafts, gears, sliders and other products due to its excellent mechanical properties. However, low carbon steel has low hardness and faces serious wear problems during service, which can easily lead to premature failure. Among them, nitriding and carburizing are the mainstream means to improve the wear resistance of the surface of low carbon steel, but the hardness of the nitrided layer and carburized layer prepared by the existing process is still very low, which is difficult to meet the friction and wear performance requirements under heavy loads, greatly limiting the industrial application of low carbon steel. In addition, the coating prepared by physical vapor deposition has high hardness and has the advantages of wear resistance and corrosion resistance, but its hardness is very different from that of the low carbon steel substrate, resulting in low coating adhesion and poor industrial application value.
[0003] In addition, although the existing vanadiumizing technology has been widely used to improve the surface hardness and wear resistance of cold working die steel, the traditional vanadiumizing process requires that the carbon content of the steel must be greater than 0.6wt.%, such as SKD11, DC53, Cr12MoV and other series of cold working die steel, whose carbon content is usually 1.0-1.3wt.%. There is no relevant report on how to use vanadiumizing technology to improve the surface hardness and wear resistance of low carbon steel.
[0004] Therefore, there is an urgent need for a vanadiumizing technology that can improve the surface hardness and wear resistance of low-carbon steel to expand the industrial application value of low-carbon steel. Summary of the invention
[0005] In order to solve the above technical problems, the present invention proposes a method and application of salt bath vanadiumizing of low carbon steel.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] The present invention provides a method for salt bath vanadiumizing of low carbon steel, comprising the following steps:
[0008] S1. Nitriding low carbon steel to obtain nitrided low carbon steel;
[0009] S2. NaCl and CaCl2 are mixed and heated to obtain a base salt; NaF is then added to the base salt, and after standing, V2O5 and Al powder are added to obtain a molten salt;
[0010] S3. The nitrided low carbon steel obtained in step S1 is immersed in the molten salt obtained in step S2 for vanadiumization to obtain nitrided and vanadiumized low carbon steel;
[0011] There is no order between step S1 and step S2.
[0012] Preferably, in step S1, the carbon content of the low carbon steel is less than 0.5wt.%.
[0013] Preferably, in step S1, the temperature of the nitriding treatment is 400-700° C., the time of the nitriding treatment is 1-20 hours, and the gas flow rate is 200-600 sccm.
[0014] Preferably, in step S2, the mass content of NaCl in the base salt is 20-80%.
[0015] Preferably, in step S2, the heating temperature is 500-1000° C., and the heating insulation time is 1-20 hours.
[0016] Preferably, in step S2, the amount of NaF added is 1-10% of the mass of the base salt.
[0017] Preferably, in step S2, the amount of V2O5 added is 10-30% of the mass of the base salt, the amount of Al powder added is 30-100% of the mass of the base salt, and the atomic ratio of V in V2O5 to Al in Al powder is (0.1-0.8):1.
[0018] Preferably, in step S3, the temperature of the vanadium treatment is 500-1000° C., the holding time of the vanadium treatment is 1-20 hours, and the cooling method of the vanadium treatment is water cooling.
[0019] The present invention provides a vanadium-diffused layer obtained by the method for vanadium-diffused low-carbon steel in salt bath described in the above technical solution.
[0020] The present invention also provides the use of the vanadium-infiltrated layer described in the above technical solution in molds, fuel cell bipolar plates or medical devices.
[0021] Compared with the prior art, the present invention has the following advantages and technical effects:
[0022] The present invention first performs nitriding treatment on low carbon steel to obtain a nitriding layer of a certain thickness, then adopts NaCl, CaCl2, NaF, V2O5 and Al powder to prepare molten salt, utilizes Al and V2O5 to undergo substitution reaction to obtain vanadium active atoms, and finally immerses the nitrided low carbon steel in molten salt for vanadiumization treatment to obtain a vanadium layer of a certain thickness, thereby greatly improving the hardness and wear resistance of the low carbon steel.
[0023] The hardness of the nitrided and vanadiumized low carbon steel prepared by the present invention is between 2700 and 3360 HV, and the wear rate is between 0.1 and 1.5×10 -15 m 3 / Nm, which is much higher than the hardness and wear resistance of the vanadium-plated low-carbon steel obtained by the traditional vanadium-plating process. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0025] Figure 1 This is a SEM image of the cross-interface structure of the vanadium-diffused layer of the nitrided and vanadium-diffused low-carbon steel prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0026] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0028] The embodiment of the present invention provides a method for salt bath vanadiumizing of low carbon steel, comprising the following steps:
[0029] S1. Nitriding low carbon steel to obtain nitrided low carbon steel;
[0030] S2. NaCl and CaCl2 are mixed and heated to obtain a base salt; NaF is then added to the base salt, and after standing, V2O5 and Al powder are added to obtain a molten salt;
[0031] S3. The nitrided low carbon steel obtained in step S1 is immersed in the molten salt obtained in step S2 for vanadiumization to obtain nitrided and vanadiumized low carbon steel;
[0032] There is no order between step S1 and step S2.
[0033] The present invention first performs nitriding treatment on low carbon steel to obtain a nitriding layer of a certain thickness, then adopts NaCl, CaCl2, NaF, V2O5 and Al powder to prepare molten salt, utilizes Al and V2O5 to undergo substitution reaction to obtain vanadium active atoms, and finally immerses the nitrided low carbon steel in molten salt for vanadiumization treatment to obtain a vanadium layer of a certain thickness, thereby greatly improving the hardness and wear resistance of the low carbon steel.
[0034] In a preferred embodiment, in step S1, the carbon content of the low carbon steel is less than 0.5wt.%, preferably ≤0.45wt.%.
[0035] In a preferred embodiment, in step S1, the temperature of the nitriding treatment is 400-700°C, preferably 450-600°C; the time of the nitriding treatment is 1-20 hours, preferably 2-10 hours; and the gas flow rate is 200-600 sccm. The present invention generates a nitriding layer on the surface of low-carbon steel through nitriding treatment, and the presence of the nitriding layer is beneficial to improving the hardness and wear resistance of low-carbon steel. The present invention controls the process parameters of the nitriding treatment within the above range, which is conducive to obtaining a dense nitriding layer.
[0036] In a preferred embodiment, in step S1, the pressure of the nitriding treatment is 20 to 300 Pa, the substrate bias is -300 to -600 V, and the duty cycle is 50 to 80%; the gases introduced during the nitriding treatment are nitrogen and argon, and the flow ratio of nitrogen to argon is (3 to 4):1.
[0037] In a preferred embodiment, the thickness of the nitrided layer in the nitrided low-carbon steel obtained in step S1 is about 2-40 μm.
[0038] In a preferred embodiment, in step S2, the mass content of NaCl in the base salt is 20-80%. In the present invention, NaCl and CaCl2 are used as base salts to play the role of flux.
[0039] In a preferred embodiment, in step S2, the heating temperature is 500-1000°C, preferably 600-1000°C, and the heating insulation time is 1-20h, preferably 2-20h.
[0040] In a preferred embodiment, in step S2, the amount of NaF added is 1-10% of the mass of the base salt. The NaF in the present invention plays a role in improving the fluidity of the melt.
[0041] In a preferred embodiment, in step S2, the standing time is 10 to 60 minutes.
[0042] In a preferred embodiment, in step S2, the amount of V2O5 added is 10-30% of the mass of the base salt, the amount of Al powder added is 30-100% of the mass of the base salt, and the atomic ratio of V in V2O5 to Al in Al powder is (0.1-0.8): 1, preferably (0.2-0.5): 1. The present invention controls the amount of V2O5 and Al powder added and the atomic ratio of V2O5 to Al powder within the above range, which is conducive to obtaining a dense vanadium-infiltrated layer, thereby greatly improving the hardness and wear resistance of low carbon steel.
[0043] In a preferred embodiment, in step S3, the temperature of the vanadium treatment is 500-1000°C, preferably 600-1000°C; the holding time of the vanadium treatment is 1-20h, preferably 2-10h; the cooling method of the vanadium treatment is water cooling. In the present invention, if the temperature of the vanadium treatment is too high, the vanadium layer will be loose and have low hardness; if the holding time is too long, the growth rate of the vanadium layer will be slow and the energy consumption will be large.
[0044] In a preferred embodiment, the thickness of the vanadiumized layer in the nitrided and vanadiumized low carbon steel obtained in step S3 is about 5 to 52 μm.
[0045] The present invention provides a vanadium-diffused layer obtained by the method for vanadium-diffused low-carbon steel in salt bath described in the above technical solution.
[0046] The present invention also provides the use of the vanadium-infiltrated layer described in the above technical solution in molds, fuel cell bipolar plates or medical devices.
[0047] The room temperature in the embodiments of the present invention refers to "25±2°C".
[0048] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources.
[0049] Example 1
[0050] A method for salt bath vanadiumizing of low carbon steel, the specific steps are as follows:
[0051] S1. 20CrMnTi steel with a carbon content of about 0.2wt.% was polished to a roughness of ≤0.1μm, and then ultrasonically cleaned with acetone and anhydrous ethanol for 30min in sequence, and blown dry with an air gun, and then placed in a plasma nitriding furnace, the furnace temperature was set to 550℃, the vacuum degree was evacuated to 20Pa, nitrogen and argon were introduced, the gas flow rate was 300sccm, the nitrogen and argon flow ratio was controlled at 3:1, the substrate bias was -500V, the duty cycle was 70%, and nitriding was performed for 5h to obtain nitrided low-carbon steel;
[0052] S2. NaCl and CaCl2 were added into a crucible in a mass ratio of 1:2, heated to 600°C, and kept warm for 2h to obtain a base salt (the mass content of NaCl in the base salt was 33.3%, and the mass content of CaCl2 was 66.7%); then 5% of the mass of the base salt was added with NaF, and the mixture was allowed to stand for 10min, and then 20% of the mass of the base salt with V2O5 and 60% of the mass of the base salt with Al powder, the atomic ratio of V in V2O5 to Al in Al powder was 0.33:1, and the temperature was adjusted to 700°C to obtain a molten salt;
[0053] S3. Immerse the nitrided low-carbon steel obtained in step S1 into the molten salt at a temperature of 700° C. obtained in step S2, keep the temperature for 5 hours, take it out and quench it in water to obtain nitrided and vanadiumized low-carbon steel.
[0054] Figure 1 This is a SEM image of the cross-interface structure of the vanadiumized layer of the nitrided and vanadiumized low carbon steel prepared in Example 1. Figure 1 It can be seen that a vanadium-infiltrated layer of a certain thickness is formed on the steel surface, and the thickness of the vanadium-infiltrated layer is about 20 μm.
[0055] Embodiments 2 to 8
[0056] The difference from Example 1 is that the nitriding temperature, nitriding time, mass ratio of V2O5 and Al powder, vanadiumizing temperature or vanadiumizing time are different, and other process parameters and steps are the same as Example 1. The differences from Example 1 are shown in Table 1.
[0057] Example 9
[0058] The difference from Example 1 is that the 20CrMnTi steel in step S1 is replaced by 08F steel, and the carbon content of 08F steel is 0.08wt.%, and the other steps and process parameters are the same as those in Example 1.
[0059] Example 10
[0060] The difference from Example 1 is that the 20CrMnTi steel in step S1 is replaced by 45 steel, and the carbon content of 45 steel is 0.45wt.%, and the other steps and process parameters are the same as Example 1.
[0061] Table 1 Process parameters of nitriding and vanadiumizing in Examples 1 to 10
[0062]
[0063] Comparative Examples 1 to 3
[0064] A method for preparing vanadiumized low carbon steel, the specific steps are as follows:
[0065] S1. 20CrMnTi with a carbon content of about 0.2wt.% (Comparative Example 1), 08F steel with a carbon content of 0.08wt.% (Comparative Example 2), and 45 steel with a carbon content of 0.45wt.% (Comparative Example 3) were polished to a roughness of ≤0.1μm, and then ultrasonically cleaned with acetone and anhydrous ethanol for 30min, and dried with an air gun to obtain pretreated low-carbon steel;
[0066] S2. NaCl and CaCl2 are added into a crucible in a mass ratio of 1:2, heated to 600°C, and kept warm for 2 hours to obtain a base salt; then NaF is added at 5% of the mass of the base salt, and the mixture is allowed to stand for 10 minutes, and then V2O5 at 20% of the mass of the base salt and Al powder at 60% of the mass of the base salt are added, wherein the atomic ratio of V in V2O5 to Al in Al powder is 0.33:1, and the temperature is adjusted to 700°C to obtain a molten salt;
[0067] S3. Immerse the pretreated low-carbon steel obtained in step S1 into the molten salt at a temperature of 950° C. obtained in step S2, keep warm for 5 hours, take out and quench in water to obtain vanadium-infiltrated low-carbon steel.
[0068] Comparative Example 4
[0069] A method for preparing vanadiumized low carbon steel by a traditional vanadiumizing process, the specific steps are as follows:
[0070] S1. The 20CrMnTi steel with a carbon content of about 0.2wt.% was polished to a roughness of ≤0.1μm, and then ultrasonically cleaned with acetone and anhydrous ethanol for 30min, and dried with an air gun;
[0071] S2. Immerse the 20CrMnTi steel treated in step S1 in a conventional vanadiumizing molten salt, keep it at 950°C for 5 hours, take it out and quench it in water to obtain a vanadiumized low-carbon steel; wherein the conventional vanadiumizing molten salt is composed of: 75.6wt.% borax, 8.4wt.% BaCl2, 10wt.% V2O5 and 6wt.% Al powder.
[0072] Performance Testing
[0073] Microhardness test: The hardness of the coatings of the vanadiumized low-carbon steel prepared in the examples and comparative examples was tested using a microhardness tester, with a test load of 100 g.
[0074] Wear resistance test: A room temperature friction and wear tester was used to test the wear rate of the coatings of the vanadiumized low carbon steel prepared in the examples and comparative examples. The smaller the wear rate, the better the wear resistance.
[0075] The coating hardness and coating wear rate of Examples 1 to 10 and Comparative Examples 1 to 4 are shown in Table 2.
[0076] Table 2 Coating properties of Examples 1 to 10 and Comparative Examples 1 to 4
[0077]
[0078]
[0079] It can be seen from Table 2 that the hardness of the nitrided and vanadiumized low carbon steels prepared in Examples 1 to 10 is between 2700 and 3360 HV, and the wear rate is between 0.1 and 1.5 × 10 -15 m 3 / Nm, its hardness and wear resistance are much higher than the hardness and wear resistance of low-carbon steel with vanadium layer obtained by traditional vanadiumizing process, and the vanadiumizing treatment of low-carbon steel is successfully realized.
[0080] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for salt bath vanadiumizing of low carbon steel, characterized in that: The following steps are involved: S1. Nitriding the low carbon steel to obtain nitrided low carbon steel; S2. NaCl and CaCl2 are mixed and heated to obtain a base salt; NaF is then added to the base salt, and after standing, V2O5 and Al powder are added to obtain a molten salt; S3. The nitrided low carbon steel obtained in step S1 is immersed in the molten salt obtained in step S2 for vanadiumization to obtain nitrided and vanadiumized low carbon steel; There is no order between step S1 and step S2.
2. The method for salt bath vanadiumizing of low carbon steel according to claim 1, characterized in that: In step S1, the carbon content of the low carbon steel is less than 0.5wt.%.
3. The method for salt bath vanadiumizing of low carbon steel according to claim 1, characterized in that: In step S1, the temperature of the nitriding treatment is 400-700° C., the time of the nitriding treatment is 1-20 hours, and the gas flow rate is 200-600 sccm.
4. The method for salt bath vanadiumizing of low carbon steel according to claim 1, characterized in that: In step S2, the mass content of NaCl in the base salt is 20-80%.
5. The method for salt bath vanadiumizing of low carbon steel according to claim 1, characterized in that: In step S2, the heating temperature is 500-1000°C, and the heating insulation time is 1-20h.
6. The method for salt bath vanadiumizing of low carbon steel according to claim 1, characterized in that: In step S2, the amount of NaF added is 1-10% of the mass of the base salt.
7. The method for salt bath vanadiumizing of low carbon steel according to claim 1, characterized in that: In step S2, the amount of V2O5 added is 10-30% of the mass of the base salt, the amount of Al powder added is 30-100% of the mass of the base salt, and the atomic ratio of V in V2O5 to Al in Al powder is (0.1-0.8):
1.
8. The method for salt bath vanadiumizing of low carbon steel according to claim 1, characterized in that: In step S3, the temperature of the vanadium treatment is 500-1000° C., the holding time of the vanadium treatment is 1-20 hours, and the cooling method of the vanadium treatment is water cooling.
9. The vanadiumized layer obtained by the method for salt bath vanadiumizing of low carbon steel according to any one of claims 1 to 8.
10. Use of the vanadium-infiltrated layer according to claim 9 in molds, fuel cell bipolar plates or medical devices.
Citation Information
Patent Citations
High-carbon steel pin roll vanadizing composite treatment process
CN101033554A
Low-carbon steel surface salt bath rare earth vanadium-titanium boronizing agent and treatment process thereof
CN103276349A
Process for the production of vanadium carbide coatings on iron
US4440581A
Chain element, chain stud and method for the production thereof
WO2014044420A1